Wildlife trade in Southern Palawan, Philippines - Cruz, Rommel M.; Van Den Beukel, Deborah V.; Widmann, Indira L.; Schoppe, Sabine; Widmann, Peter (2007)
Southern Palawan is one of the hottest hotspots for illegal trade of wildlife in the Philippines. Large numbers of wildlife are transported either by fishing vessels of private chartered planes from the south of Palawan to Zamboanga, Cebu, Manila, Batangas and even to Malaysia. Parrots and mynas are among the species of birds most traded due to their huge demand in the market. Other birds that are also under considerable pressure of poaching are Palawan hornbill and White-bellied sea eagle. Apart from birds, other Palawan wildlife included in the illegal shipments are Palawan pangolin, Balabac mouse deer, Palawan bearcat, Palawan bearded pig, Southern Palawan tree squirrel, freshwater turtles and beetles. The present study identified species of conservation priority involved in trade. The study also presents data on traded wildlife species in Palawan including their market value, modes of transport, operation of wildlife traders in Palawan and trade routes.
Keywords: Wildlife trade; Palawan Island (Philippines); Wildlife trade -- Palawan